(untitled) (Journal of the College of Basic Education, 2024)
The present study attempts to identify the future training needs of male and female teachers of students in special education classes from their points of view. The study designated to verify the significance of statistical differences in male and female teachers’ estimation for the training needs necessary for them in teaching students in special education classes according to the variables of gender (males - females), and the years of service. Data analysis of this study focused on descriptive approach. A purposeful sampling was used consisting of (100) male and female teachers, dividing into (50) for male and (50) for female teachers, collecting a data from the General Directorates of Education of Baghdad Governorate, Rusafa First, Second, and Third, as they were chosen by stratified random sample. In order to seek the objectives of this study, the researcher built a measure of the future training needs of male and female teachers of the educational students’ classes. According to their points of view, it consists of six areas and (47) items. The five-point scale was adopted in this study. The current study has provided valuable results. These are as the followings: 1) The field of planning and implementing of the educational process ranked in the first level with an average ability( 4,089), 2) the field of employing technology and educational methods in education ranked in the second level with an average of (3,974), 3) the field of behavior modification and change methods ranked in the third level with an average of (3,727), 4)the field of managing educational experiences in educational integration ranked in the fourth level with an average of (3,570), 5) the field of teaching methods and strategies ranked in the fourth level, 6) active learning ranked in the fifth level with an average of (3,385), 7) and the field of diagnosing and evaluating people with special needs ranked in the sixth level with an average of (3,278). In general, however, the present findings confirm that the needs were arranged in descending order, as the arithmetic averages ranged between (4,025) and (3,200), these reveal a difference of (0.825) between the highest and lowest arithmetic averages, and there were no statistically significant differences between the arithmetic averages of the sample members’ estimating on the tool due to the variables of both (gender and the years of service) of the male and female teachers of students in special educational classes.